2014
DOI: 10.9778/cmajo.20130076
|View full text |Cite
|
Sign up to set email alerts
|

Use of benzodiazepines and related drugs in Manitoba: a population-based study

Abstract: Background: Despite their favourable toxicology profile, benzodiazepines and the related Z-drugs (zopiclone, zolpidem and zaleplon) have been associated with physiological tolerance, dependence and addiction. Evidence of harm (e.g., falls, motor vehicle collisions and cognitive disturbances) has been reported in older populations. The aim of this study was to determine the relation between users' characteristics and the use of benzodiazepines and Z-drugs in Manitoba over a 16-year period. Methods:This time-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 30 publications
9
64
1
1
Order By: Relevance
“…3,50 Similar to previous studies, 7,8,14,20,51 we found adults had increased odds of long-term sedative use if they were women, if they had low incomes and if they had relatively poor health status. We also found that having a surname of Chinese or South Asian origin was associated with a protective effect on the odds of long-term sedative use.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…3,50 Similar to previous studies, 7,8,14,20,51 we found adults had increased odds of long-term sedative use if they were women, if they had low incomes and if they had relatively poor health status. We also found that having a surname of Chinese or South Asian origin was associated with a protective effect on the odds of long-term sedative use.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, because some prescriptions will be written but not filled, this measure is arguably an understatement of the extent of long-term sedative prescribing in BC. Although our findings mirror recent trends in total benzodiazepine and z-drug dispensations from another Canadian province, 8 it is important to note that they are based on BC's population and may not be generalizable to other jurisdictions with different prescription monitoring programs and deprescribing strategies in place.…”
Section: Limitationscontrasting
confidence: 55%
“…This study examined prescribing trends for benzodiazepines and Z‐drugs in Ireland from 2005 to 2015 using national pharmacy claims data for the GMS population aged ≥16 years. An overall significant reduction in benzodiazepine prescribing was observed, coupled with significant increases in Z‐drug prescribing, which mirrors trends observed in other countries . However, it is difficult to make direct comparisons between the observed prescribing rates and those reported in other countries because of differences in the nature of the dataset, sample population and time periods examined .…”
Section: Discussionmentioning
confidence: 76%
“…3437 , though international findings about benzodiazepine prescribing have been more mixed. 34,35,38,39 …”
Section: Discussionmentioning
confidence: 99%